A Sensitive and Selective Electrochemical Aptasensor for Carbendazim Detection - Suthira Pushparajah; Mahnaz Shafiei; Aimin Yu (Biosensors)
Carbendazim (CBZ) is used to prevent fungal infections in agricultural crops. Given its high persistence and potential for long-term health effects, it is crucial to quickly identify pesticide residues in food and the environment in order to mitigate excessive exposure. Aptamer-based sensors offer a promising solution for pesticide detection due to their exceptional selectivity, design versatility, ease of use, and affordability. Herein, we report the development of an electrochemical aptasensor for CBZ detection. The sensor was fabricated through a one-step electrodeposition of platinum nanoparticles (Pt NPs) and reduced graphene oxide (rGO) on a glassy carbon electrode (GCE). Then, a CBZ-specific aptamer was attached via Pt-sulfur bonds. Upon combining CBZ with the aptamer on the electrode surface, the redox reaction of the electrochemical probe K4[Fe(CN)6] is hindered, resulting in a current drop. Under optimized conditions (pH of 7.5 and 25 min of incubation time), the proposed aptasensor showed a linear current reduction to CBZ concentrations between 0.5 and 15 nM. The limit of detection (LOD) for this proposed aptasensor is 0.41 nM. Along with its repeatable character, the aptasensor demonstrated better selectivity for CBZ compared to other potential compounds. The recovery rates for detecting CBZ in skim milk and tap water using the standard addition method were 98% and 96%, respectively. The proposed aptasensor demonstrated simplicity, sensitivity, and selectivity for detecting CBZ with satisfactory repeatability. It establishes a strong foundation for environmental monitoring of CBZ.